Effect of biological agents on B-lymphocyte subpopulations in patients with systemic lupus erythematosus - A. A. Mesnyankina; S. K. Solovyev; E. A. Aseeva; A. P. Aleksankin; E. N. Aleksandrova; E. L. Nasonov (Современная ревматология)
Objective: to evaluate the effect of different biological agents (BAs), including rituximab (RTM) and belimumab (BLM) combination therapy, on B-lymphocyte subpopulations during a follow-up of patients with systemic lupus erythematosus (SLE).Patients and methods. The investigation enrolled 64 patients with a verified diagnosis of SLE with high and moderate disease activities according to the Systemic Lupus Erythromatosus Disease Activity Index (SLEDAI)-2K scores; 47patients of them took RTM, 10 used BLM, and 7 received RTM + BLM combination therapy. Peripheral blood B-lymphocyte subpopulations were measured by multicolor flow cytofluorom-etry, using a panel of monoclonal antibodies to B-lymphocyte surface membrane markers. The results were assessed using the SLEDAI-2K scores and the British Isles Lupus Assessment Group (BILAG) index.Results and discussion. RTM therapy led to a marked decrease in major B-lymphocyte populations, the residual cells being naXve B-cells and different memory B cell populations, the percentage of which depended on the degree of depletion after a RTM cycle. Incomplete B-lymphocyte depletion was associated with the large baseline numbers of plasma cells (PCs) (>0.2%). One year after initiation of therapy, the percentage ratio of B-lymphocyte subpopulations returned almost completely to baseline values, except the whole memory B-cellpopulation. BLM therapy resulted in a decrease in PCs and plasmablasts (PBs) to the point of their complete depletion. There were reductions in total CD19+ B-lym-phocytes and naive B lymphocytes. The use of the combination of BAs permitted the monitoring of the total B-lymphocyte population; its slower recovery was seen in patients with its complete depletion after a rituximab cycle. The therapy promoted maintenance of low concentrations of PCs and PBs, total memory B-cell and naive B-cell populations.Conclusion. In patients with SLE, all the three therapy with BAs demonstrated a good efficiency manifested by a decrease in clinical and laboratory disease activity. The found time course of changes in B-lymphocyte subpopulations can be used for the selection of therapy and for the evaluation of its efficacy.